Substitution reactivity and structural variability induced by tryptamine on the biomimetic rhenium tricarbonyl complex. Issue 39 (13th July 2021) - Jacobs, Frederick J. F.; Venter, Gertruida J. S.; Fourie, Eleanor; Kroon, Robin E.; Brink, Alice
Abstract : The biomimetic tryptamine rhenium tricarbonyl complex shows rapid substitution reactivity on the 6th position as well as cytotoxicity and photoluminescence capability induced by the salicylidene bidentate ligand. Abstract : A series of seven fac -[Re(CO)3 (5Me-Sal-Trypt)(L)] complexes containing tryptamine on the N, O 5-methyl-salicylidene bidentate ligand backbone and where L is MeOH, Py, Imi, DMAP, PPh3 coordinated to the 6th position have been studied, including the formation of a dinuclear Re2 cluster. The crystallographic solid state structures show marked similarity in structural tendency, in particular the rigidity of the Re core and the hydrogen bond interactions similar to those found in protein structures. The rates of formation and stability of the complexes were evaluated by rapid time-resolved stopped-flow techniques and the methanol substitution reaction indicates the significant activation induced by the use of the N, O salicylidene bidentate ligand as manifested by the second-order rate constants for the entering nucleophiles. Both linear and limiting kinetics were observed and a systematic evaluation of the kinetics is reported clearly indicating an interchange type of intimate mechanism for the methanol substitution. The anticancer activity of compounds 1–7 was tested on HeLa cells and it was found that all compounds showed similar cytotoxicity where solubility allowed. IC50 -values between ca. 11 and 22 μM indicate that some cytotoxicity resides most likely on the salicylidene–tryptamine ligand. The photoluminescence of the seven complexes is similar in maximum emission wavelength with little variation despite the broad range of ligands coordinated to the 6th position on the metal centre.